Ready, Set, Go! * Short Course Leader’s Guide - Domsch, Ann; Johannes, Elaine; Mack, Diane; Sanders-Hahs, Erin (My University, 2008)
The goal of Ready, Set, Go! is to create awareness and to generate community support for military-connected youth and families who are geographically dispersed.
EP151_2008-09
Keywords: EP151; Home and Family; 4-H Youth Development; EP